Lateral and crestal sinus lift complications: a retrospective comparative study - Stoichkov, Biser B. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: To explore the relationship between the operative methods for sinus lifting and related intra-and postoperative complications. Methods: 47 cases of sinus lift were traced, with 118 implants placed. 83 of them after lateral sinus lifting and 35 with a crestal approach. Presence of bone septum, thickness of the sinus membrane, bone density, and the height of residual bone were tracked out preoperatively, as prerequisites of complications during and after implant placement in the distal parts of the maxilla. Results: In eight cases (17.02%), sinus membrane perforations occurred. The most common location of the tearing was close to the lower medial edge of the bone window. After fixing perforation, a total of 37 implants were placed under these conditions. In three of them (5.41%), poor osseointegration was found after six mounts. Statistically significant impact of the thickness of the sinus membrane in cases of membrane tearing was found. Conclusions: Increasing the height of the available bone in the distal areas of the maxilla by elevating the maxillary sinus floor is a safe and predictable procedure. Both the crestal and lateral approaches have a high success rate. All possible complications during the operation need to be analyzed in advance, and when they occur, it is mandatory to fix them adequately. Therefore, a careful consideration of the local and systemic conditions affecting implant survival is essential for successful implant treatment.